Antifouling performance of TiO2-based SiO2-Na2O-K2O glass-ceramic coatings in marine environments - Daloglu, Sinan; Copoglu, Nurullah; Karaahmet, Oguz; Cicek, Bugra (ELSEVIER SCIENCE SA, 2024)
Biofouling refers to the accumulation of organisms on artificial surfaces. This phenomenon poses significant challenges in industrial processes, including reduced energy efficiency and increased fuel consumption. Antifouling coating systems are designed to prevent biofouling on artificial surfaces. Currently, there is a growing focus on developing eco-friendly solutions to mitigate the environmental impact of these antifouling coatings. In this study, the antifouling (AF) performance of a TiO2-based borosilicate glass-ceramic coating (Ti-GCC) system was evaluated in terms of barnacle settlement on the coating surface. To create anatase crystals in a coating, a special precursor glass (Ti-PG) formulation, Na2O-K2O-TiO2-B2O3-Al2O3-SiO2-P2O5-F, with <10 % of Na2O and 20 % TiO2 along with other components was used. The Ti-PG was characterised through X-ray fluorescence (XRF) spectroscopy to determine the chemical composition. The milled Ti-PG with additives was applied on a steel substrate using a spray gun and devitrified at 550 degrees C and 860 degrees C for 6 min. The phase determination, surface evaluation, thermal behaviour analysis, and AF evaluation of the Ti-GCC were conducted through X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), non-contact optical profilometry (NCOP), and thermogravimetric-differential thermal analysis (TG-DTA). The anatase crystal was determined to exist in the Ti-GCC structure. Although the AF evaluation results revealed that the Ti-GCC system had barnacle settlement (73.9 barnacles/cm(2)), the surface could be easily cleaned. Additionally, the EDS results confirmed that no biofilm was formed on the Ti-GCC's surface. The roughness of the surface before the AF evaluation and after the cleaning procedure was measured using NCOP, and the difference in surface roughness was examined. The small difference in the roughness of the surfaces suggested that the Ti-GCC system exhibited resistance to microbially induced corrosion (MIC). Furthermore, EDS mapping did not provide any evidence of barnacle diffusion into the coated layer. Furthermore, the thickness measurements of the cross-sectional area of the Ti-GCC before and after AF evaluation through SEM proved that coating depletion did not occur.
Keywords: Glass -ceramic; Antifouling; Barnacle settlement; Coating; Surface roughness; Microbially induced corrosion; MICROBIOLOGICALLY INFLUENCED CORROSION; BIOFILM; BACTERIA; SURFACES; BEHAVIOR; ANATASE; STEEL; Materials Science